1994
DOI: 10.1111/j.2042-7158.1994.tb03865.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacokinetic and Pharmacodynamic Properties of Oral and Intravenous (+)-Sotalol in Healthy Volunteers

Abstract: The pharmacokinetic and pharmacodynamic properties of (+)-sotalol (BMY-5763) were studied to analyse the relationship between plasma concentration and QTc prolongation in healthy male volunteers given single oral doses of 50, 100, 200 and 300 mg, repeated oral doses of 200 mg twice daily for 6.5 days, and single intravenous doses of 1.0 and 1.5 mg kg-1. The plasma concentration of (+)-sotalol peaked about 3 h after oral administration and declined with a half-life of 7.9-9.7 h. The Cmax and AUC showed dose-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 15 publications
3
30
0
Order By: Relevance
“…(+)-Sotalol effects on QTc intervals in healthy male subjects were analyzed in the work by Uematsu et al 47 The authors did not report the correction method used. The drug was administered orally and intravenously, and in the latter case PK-PD modeling was attempted.…”
Section: Pharmacokinetic-pharmacodynamic Modeling Of Qt Prolongationmentioning
confidence: 99%
“…(+)-Sotalol effects on QTc intervals in healthy male subjects were analyzed in the work by Uematsu et al 47 The authors did not report the correction method used. The drug was administered orally and intravenously, and in the latter case PK-PD modeling was attempted.…”
Section: Pharmacokinetic-pharmacodynamic Modeling Of Qt Prolongationmentioning
confidence: 99%
“…M-4 was mainly excreted in urine in healthy human volunteers (4). The excretion of M-4 in urine after the oral administration of BOF-4272 to the cynomolgus monkey was lower than that in healthy human volunteers (4), and was about 1/10 that after intravenous administration.However, it is thought that the low excretion of M-4 in urine after the oral administration of BOF-4272 to the cynomolgus monkey is not due to low biotransformationbut to low absorption from the gastrointestinal tract. These findings suggest that the cynomolgus monkey may be a suitable animal species for evaluating the clinical pharmacokinetics and biotransformation of BOF-4272.…”
Section: Preparation Of Urine Samples For Hplcmentioning
confidence: 99%
“…It has also been demonstrated that the linear range of absorption and/or elimination of BOF-4272 is very wide in the mouse and the rat (11). It has been shown that BOF-4272 is rapidly biotransformed to a main metabolite (M-4, a sulfoxidecontaining metabolite of BOF-4272), that M-4 is then mainly excreted in urine, and that BOF-4269 is a minor metabolite in plasma after oral administration to healthy volunteers (4). It has been suggested that we should clarify the metabolic pathways of BOF-4272 in the rat (12) and the dog (13).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations